(untitled) (Nativa, 2017)
Este trabalho foi desenvolvido com o objetivo de estudar o potencial de enraizamento de estacas de grumixameira (Eugenia brasiliensis), tratadas com diferentes concentrações de reguladores de crescimento em ambientes de cultivo. Estacas herbáceas foram coletadas de plantas matrizes. As estacas tinham entre 8 e 10 cm de comprimento. Foram deixados dois pares de folhas e duas a três gemas por estaca. Os tratamentos consistiram na combinação entre dois ambientes de cultivo (câmara de nebulização e mini estufas) e dois tipos de hormônios (GA3 e 2,4-D) em quatro doses (0,00; 0,05, 0,10, 0,20 mg L-1). O delineamento foi em blocos ao acaso em esquema fatorial (2 x 2 x 4) com três repetições e dez estacas por parcela. Foram avaliadas 100 dias após o plantio, as porcentagens de estacas enraizadas, estacas vivas, formação de calos e número de raízes emitidas por estaca. Conclui-se que para a aplicação dos hormônios vegetais não houve diferenças significativas entre os tratamentos, porém houve resultado mais significativo para as dosagens intermediárias de GA3 e 2,4-D, sendo que o ambiente mini estufa foi mais eficiente em relação a sobrevivência. Palavras-chave: Eugenia brasiliensis, propagação, hormônio. GRUMIXAMA PROPAGATION IN GROWTH REGULATORS FUNCTION AND CULTIVATION ENVIRONMENTS ABSTRACT This paper was developed with the goal of studying the potential of rooting grumixameira cuttings (Eugenia brasiliensis) that have beentreated with different concentrations of growth regulators and cultivation environments. Herbaceous cuttings were collected from mother plants. The cuttings were between 8 and 10 cm, which resulted in two to three gems per cutting. The treatments included two growing environments and two hormone types in five doses. The environments consisted of a nebulization chamber and a micro chamber made with pet bottles. GA3 and 2,4-D were the plant growth regulators used in four concentrations (0, 0.5, 0.1 and 0.2 mg L-1). The delimitation was in randomized blocks in factorial (2 x 2 x 4) with three repetitions and ten cuttings per portion. After 100 days of plantation, the percentage of rooted cutting, live cutting, formation of calluses and number of roots issued per cutting was examined. It’s possible to conclude that, for the application of vegetables hormones, there weren’t relevant difference between both, although there was a more significant result for the intermediate doses of GA3 and 2,4-D, in which the micro chamber greenhouse was the more efficient in relation with survival of cuttings. Keywords: Eugenia brasiliensi, propagation, hormone. DOI: http://dx.doi.org/10.5935/2318-7670.v05n02a06